How Principals Cultivate Teacher Personal Competencies: Insights from Study Group Implementation in Elementary Schools - Arief Nur Afghan; Nana Herdiana Abdurrahman (Papanda Publisher, 2026)
Teacher personal competencies, encompassing integrity, emotional stability, and professional ethics, are fundamental to quality elementary education, yet their systematic development remains underexamined. This study analyzes how principal management through the POAC framework enhances teacher personal competencies via study groups. A qualitative case study design was employed at SDN Ciseureuh and SDN Karya Bhakti in Cianjur Regency, Indonesia. Data were collected through in-depth interviews, participatory observation, and document analysis from principals, teachers, and stakeholders selected through purposive and snowball sampling. Data analysis followed Miles et al.'s (2014) three-stage inductive process, with trustworthiness established through triangulation, member checking, and audit trails. Findings reveal that systematic principal management—encompassing evidence-based planning, strategic resource organization, motivational leadership, and continuous evaluation—effectively strengthens teacher integrity, responsibility, discipline, and professionalism through study groups. Study groups structured around collaborative inquiry and reflective practice created authentic learning environments. However, time constraints, motivational variation, and infrastructure limitations emerged as implementation challenges, while principal commitment, competent facilitation, and collegial culture served as facilitating factors. An unexpected finding showed differential impact across career stages, with early-career teachers experiencing more transformative changes than veterans. The integration of POAC management theory with professional learning community research demonstrates that teacher personal competencies are developable through intentional, well-managed collegial learning. This culturally contextualized approach offers practical guidance for principals and contributes theoretically by synthesizing management, professional development, and character education literature.